Intraoperative Laparoscopic Near-Infrared Fluorescence Cholangiography to Facilitate Anatomical Identification: When to Give Indocyanine Green and How Much. (August 2016) - Zarrinpar, Ali; Dutson, Erik P.; Mobley, Constance; Busuttil, Ronald W.; Lewis, Catherine E.; Tillou, Areti; Cheaito, Ali; Hines, O. Joe; Agopian, Vatche G.; Hiyama, Darryl T.
Recent technological advances have enabled real-time near-infrared fluorescence cholangiography (NIRFC) with indocyanine green (ICG). Whereas several studies have shown its feasibility, dosing and timing for practical use have not been optimized. We undertook a prospective study with systematic variation of dosing and timing from injection of ICG to visualization. Adult patients undergoing laparoscopic biliary and hepatic operations were enrolled. Intravenous ICG (0.02-0.25 mg/kg) was administered at times ranging from 10 to 180 minutes prior to planned visualization. The porta hepatis was examined using a dedicated laparoscopic system equipped to detect NIRFC. Quantitative analysis of intraoperative fluorescence was performed using a scoring system to identify biliary structures. A total of 37 patients were enrolled. Visualization of the extrahepatic biliary tract improved with increasing doses of ICG, with qualitative scores improving from 1.9 ± 1.2 (out of 5) with a 0.02-mg/kg dose to 3.4 ± 1.3 with a 0.25-mg/kg dose ( P < .05 for 0.02 vs 0.25 mg/kg). Visualization was also significantly better with increased time after ICG administration (1.1 ± 0.3 for 10 minutes vs 3.4 ± 1.1 for 45 minutes, P < .01). Similarly, quantitative measures also improved with both dose and time. There were no complications from the administration of ICG. These results suggest that a dose of 0.25 mg/kg administered at least 45 minutes prior to visualization facilitates intraoperative anatomical identification. The dosage and timing of administration of ICG prior to intraoperative visualization are within a range where it can be administered in a practical, safe, and effective manner to allow intraoperative identification of extrahepatic biliary anatomy using NIRFC.